Insights on Cancer Cell Inhibition, Subcellular Activities, and Kinase Profile of Phenylacetamides Pending 1H-Imidazol-5-One Variants - Khayat, Maan T.; Omar, Abdelsattar M.; Ahmed, Farid; Khan, Mohammad I.; Ibrahim, Sara M.; Muhammad, Yosra A.; Malebari, Azizah M.; Neamatallah, Thikryat; El-Araby, Moustafa E. (Frontiers in Pharmacology, 2022)
Structural changes of small molecule drugs may bring interesting biological properties, especially in the field of kinase inhibitors. We sought studying tirbanibulin, a first-in-class dual Src kinase (non-ATP competitive)-tubulin inhibitor because there is no enough reporting about its structure-activity relationships. In particular, the present research is based on the replacement of the outer ring of the biphenyl system of 2-[(1,1'-biphenyl)-4-yl]-N-benzylacetamide, the identified pharmacophore of KX chemotype, with a heterocyclic ring. The newly synthesized compounds showed a range of activities in cell-based anticancer assays, agreeing with a clear SAR profile. The most potent compound, (Z)-N-benzyl-4-[4-(4-methoxybenzylidene)-2-methyl-5-oxo-4,5-dihydro-1H-imidazol-1-yl]phenylacetamide (KIM-161), demonstrated cytotoxic IC50 values at 294 nM and 362 nM against HCT116 colon cancer and HL60 leukemia cell lines, respectively. Profiling of this compound (aqueous solubility, liver microsomal stability, cytochrome P450 inhibition, reactivity with reduced glutathione and plasma protein binding) confirmed its adequate drug-like properties. Mechanistic studies revealed that this compound does not depend on tubulin nor Src kinase inhibition as a factor in forcing HL60 to exit its cell cycle and undergo apoptosis. Instead, this compound downregulated several other kinases such as members of BRK, FLT and JAK families. It also strongly suppresses signals of ERK1/2, GSK-3α/β, HSP27 and STAT2, while it down-regulated AMPKα1 phosphorylation within the HL60 cells